Investigating the in vitro regeneration potential of selected local rice cultivars in Bangladesh - Hasan, Rashidul; Bhuiyan, Mohammed Shafi Ullah; Deb, Goutam; Dina, Mst Maiful Akter; Sultana, Sayeda (Fundamental and Applied Agriculture, 2020)
The study was conducted to establish a suitable protocol for in vitro re- generation of local rice (Oryza sativa) cultivars grown in greater Sylhet re- gion in Bangladesh for further genetic improvement through biotechnolog- ical manipulation. To figure out the optimum medium for high frequency callus induction and shoot regeneration, dehusked seeds of O. sativa cv. Lakhai were cultivated on Murashige and Skoog (MS) medium strengthened with several concentrations of 2,4-Dichlorophenoxy acetic acid (2,4-D), α- Napthalene acetic acid (NAA) and 6-Benzylaminopurine (BA). In response to plant growth regulators, the ranges of callus and shoot induction frequency of cv. Lakhai were 13.33% to 100% and 6.66 to 93.33%, respectively. The highest frequency (100%) of callus initiation was found in MS medium sup- plemented with 3 mg L−1 NAA and 1.0 mg L−1 BA and the lowest callus initiation (13.33%) was noticed in MS medium with 1.0 mg L−1 NAA. The highest shoot regeneration (93.33%) was found in MS medium comprised with 0.5 mg L−1 NAA and 3.0 mg L−1 BA. Thereafter, the callus and shoot regeneration potentials of five selected local cultivars including cv. Lakhai were evaluated using the most responsive medium standardized to cultivar Lakhai. The cv. Lakhai showed the greatest shoot regeneration frequency (93.33%) and the lowest frequency (53.33 %) was observed in cv. Maloti. MS media fortified with 0.1-0.2 mg L−1 NAA gave the maximum frequency (100%) for root initiation. When the plantlets were grown enough with root, they were acclimatized in pot soil and grown up to maturity stage in field con- ditions. Thus, the developed protocol for callus induction and regeneration of rice plantlet can be implemented for various biotechnological practices related to genetic improvement of Bangladeshi local rice cultivars.